ケンキュウ ショウシュウカイ ゲンチ カンソク ニ ヨル キョクイキ カイヨウ ノ ヘンドウ カテイ ノ ケンキュウ ホウコク - 牛尾, 収輝; ウシオ, シュウキ; Ushio, Shuki (1999)
P(論文) 本研究小集会の目的は, 極域海洋の変動過程および気候変動との関連を解明するための将来の研究計画について議論することである。オホーツク海や南大洋で実施された現地観測, 数値的研究, および衛星や気候データの解析結果に基づく話題が提供された。また今後の現地観測を展開する上で, 観測船の必要性が強調され, 具体的な観測計画が提案された。 The purpose of the present workshop is to discuss future research plans to reveal variability in polar oceans and their relation to global climate change. Several topics dealing with field observations, theoretical studies, and data analyses concerning the Sea of Okhotsk and the Southern Ocean were presented. Furthermore, the necessity of research vessels was stressed and observation plans were proposed to promote polar oceanography in the Southern Ocean. departmental bulletin paper